Homeobox transcription factor OsZHD2 promotes root meristem activity in rice by inducing ethylene biosynthesis. (25th May 2020) - Yoon, Jinmi; Cho, Lae-Hyeon; Yang, Wenzhu; Pasriga, Richa; Wu, Yunfei; Hong, Woo-Jong; Bureau, Charlotte; Wi, Soo Jin; Zhang, Tao; Wang, Rongchen; Zhang, Dabing; Jung, Ki-Hong; et al.
Abstract : The regulatory factor ZHD2 promotes root meristem activity and affects grain yield in rice by inducing ethylene biosynthesis. Abstract: Root meristem activity is the most critical process influencing root development. Although several factors that regulate meristem activity have been identified in rice, studies on the enhancement of meristem activity in roots are limited. We identified a T-DNA activation tagging line of a zinc-finger homeobox gene, OsZHD2, which has longer seminal and lateral roots due to increased meristem activity. The phenotypes were confirmed in transgenic plants overexpressing OsZHD2 . In addition, the overexpressing plants showed enhanced grain yield under low nutrient and paddy field conditions. OsZHD2 was preferentially expressed in the shoot apical meristem and root tips. Transcriptome analyses and quantitative real-time PCR experiments on roots from the activation tagging line and the wild type showed that genes for ethylene biosynthesis were up-regulated in the activation line. Ethylene levels were higher in the activation lines compared with the wild type. ChIP assay results suggested that OsZHD2 induces ethylene biosynthesis by controlling ACS5 directly. Treatment with ACC (1-aminocyclopropane-1-carboxylic acid), an ethylene precursor, induced the expression of the DR5 reporter at the root tip and stele, whereas treatment with an ethylene biosynthesis inhibitor, AVG (aminoethoxyvinylglycine), decreased that expression in both the wild type and the OsZHD2 overexpression line. These observations suggest that OsZHD2 enhances root meristem activity by influencing ethylene biosynthesis and, in turn, auxin.